Sexual identity, coming out, and romantic relationships among self-confessed college tomboys and lesbians - Cabungcal, Kristine Mae C.
This study described the sexual identity, coming out, and romantic relationships among self-confessed college tomboys and lesbians. The tomboys were found to assume more a masculine role, while lesbians the feminine role. Results showed that a greater number of respondents (50%) had experienced sexual identity confusion during their elementary years. The same percentage of respondents also reported that it was at the age of 15 that they first realized that they were homosexuals. All of the respondents are clear of their sexual identity and have fully accepted themselves. The respondents were open to their friends. While open to their friends, they remain to be closeted at home due to the stigma that is attached by their family members to tomboys and lesbians.